A novel approach to personalising the mechanical properties of sprint footwear - Toon, D.; Majewski, C.; Zarringhalam, H.; Hopkinson, N.; Caine, M. (The Engineering of sport 7, Volume 2, 2008)
A novel method for adapting the mechanical properties of sprint shoe sole units is explored. Five different ratios of glass to nylon were mixed and laser sintered to produce Standard test samples and sprint shoe sole units. Samples were subjected to Standard tensile test procedures and sole units were tested in a purpose built fixture. In-filling nylon-12 with higher ratios of glass increased longitudinal bending stiffness. The mean force in extension over the tested range was 8.9 and 16.0 N for the 0% and 50% glass filled sole units respectively. The mean force in flexion over the tested range was 11.6 and 17.7N for the 0% and 50% glass filled sole units. However, increased stiffness comes at the expense of ductility and mechanical evaluation over the shoes functional range resulted in mechanical failure for the sole units in-filled with 50% glass. Further work on alternative base and infill materials needs to be conducted before the technique is suitable for functional footwear. Key words: Footwear personalisation; stiffness; sprinting; selective laser sintering; design.